Pengaruh NPF, FDR dan BOPO Terhadap Profitabilitas Pada BCA Syariah (Periode 2015-2022) - Muztaba, M; Suryani, Suryani; Hasanah, Irmatul (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to determine the influence of Non-Perfoming Financing (NPF), Financing to Deposit Ratio (FDR) and Operating Costs of Optional Income (BOPO) on profitability (ROA) and (ROE) in BCA Syariah for the 2015-2022 period. This study uses a quantitative method with secondary data obtained from the official website of BCA Syariah. The sampling method through purposive sampling with research data analysis techniques includes classical assumption test, multiple linear regression test, and hypothesis test, The conclusion of the hypothesis test partially shows that NPF and FDR have no effect on Profitability (ROA), while FDR and BOPO have no effect on Profitability (ROE) in BCA Syariah. Meanwhile, simultaneously Non-Perfoming Financing (NPF), Financing to Deposit Ratio (FDR) and Operating Income Ratio (BOPO) affect the Profitability (ROA) of BCA Syariah. This is different from the ROE results which show that simultaneously Non-Perfoming Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Income Ratio (BOPO) have no effect on the Profitability (ROE) of BCA Syariah